(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
The Periwinkle shell (Tympanotonus fuscatus) is one of the most abundant wastes in the Calabar coastal region of Nigeria and needs to be put into proper use. The great need to shift attention towards waste materials with good mechanical properties to replace some materials used in the Automobile industries for Automobile products is paramount. This research focused on the Mechanical characterization of several composites developed from Periwinkle Shell Powder (PSP) as filler and four selected polymeric materials as the matrix. Recycled high-density polyethylene (rHDPE), Recycled linear low-density polyethylene (rLLDPE), Recycled polystyrene (rPP) and recycled polystyrene (rPS) from waste dumps were selected as the Matrix for the composites. The crushed periwinkle shell (CPSP) was subjected to a calcination (ashing) process. Ashed Periwinkle Shell Powder (APSP) was used to reinforce the rHDPE, rLLDPE, rPP and rPS at 0 to 40% filler loading. Mechanical tests carried out resulted in the 30%PSP and 70%PP composite having better tensile and flexural strengths, good flexural modulus, hardness, impact and moisture absorption results. Results obtained from the mechanical tests were comparable with values obtained from a tested existing vehicle bumper. The APSP-filled recycled polymer composites can serve as a suitable green alternative to existing vehicle bumpers.